A first look at mitochondrial genetic diversity in Miniopterus schreibersii in Serbia - Bajić, Branka; Budinski, Ivana; Rajičić, Marija; Miljević, Milan; Rončević, Aleksa; Blagojević, Jelena (Archives of Biological Sciences, 2024)
Paper description: Miniopterus schreibersii genetic diversity across its distribution has been explored using mitochondrial and nuclear markers, but without representation from Serbia. The mitochondrial hypervariable region 1 (HV1) gene fragment was screened to assess the genetic diversity of Serbian schreibersii and its relatedness to European and Asia Minor samples. Nine haplotypes, including 6 new ones, were found, indicating connectivity with Europe and Anatolia. The haplotype network suggested a single refugium origin and sudden population expansion. The genetic data for the Balkan region enhance our understanding of schreibersii population structure and support a previous hypothesis about its Anatolian origin. Abstract: Schreiber’s bent-winged bat Miniopterus schreibersii (Chiroptera) is a widespread, cave-dwelling, regionally migrating species whose genetic diversity was studied throughout its distribution area using mitochondrial and nuclear markers. Previous studies revealed little to no structuring of populations and established Anatolia to be a single refugium during the last glacial maximum. The Balkans were well covered in these studies but usually lacked samples from Serbia. We sequenced the mitochondrial hypervariable region 1 (HV1) gene in M. schreibersii collected at seven sites in Serbia to assess their genetic relatedness to other European and Asia Minor populations and check whether the Balkans exhibit a higher genetic diversity than Western Europe due to its closeness to Anatolia. We recorded nine haplotypes from Serbia, six of which had not been previously reported, with a haplotype diversity of 0.585. The remaining three were shared with individuals from Portugal, Greece, and Turkey. A single most common haplotype was present throughout the species distribution range, pointing to a well-connected population and as indicated by the shape of the haplotype network, a common origin, and a sudden population expansion. Results complement existing data on M. schreibersii having a non-structured population, adding valuable new data from the Balkans supporting the previous hypothesis about its Anatolian origin.